2013
DOI: 10.1007/s00404-012-2681-z
|View full text |Cite
|
Sign up to set email alerts
|

Robot-assisted hysterectomy compared to open and laparoscopic approaches: systematic review and meta-analysis

Abstract: Compared to open surgery, robot-assisted hysterectomy offers benefits for reduced length of hospital stay and blood transfusions. The best evidence of improved outcomes is for simple total hysterectomy with node staging. Study quality was poor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 42 publications
3
52
0
2
Order By: Relevance
“…Furthermore, the robotic approach resulted in fewer complications for women who underwent simple total hysterectomy with nodal staging [52]. Another meta-analysis of 22 studies that evaluated surgical treatment in women with endometrial cancer concluded that robotic surgery, although more efficient, had higher surgical complication rates than laparoscopic surgery [51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the robotic approach resulted in fewer complications for women who underwent simple total hysterectomy with nodal staging [52]. Another meta-analysis of 22 studies that evaluated surgical treatment in women with endometrial cancer concluded that robotic surgery, although more efficient, had higher surgical complication rates than laparoscopic surgery [51].…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto al sangrado severo y la necesidad de transfusiones está descrita una media de 0,8%-2,7%, en nuestra serie ninguna paciente requirió transfusión de glóbulos rojos (22,27) . No hubo complicaciones urinarias crónicas en nuestra serie.…”
Section: Discussionunclassified
“…2 Furthermore, a high risk of bias was evident in these studies, with no randomisation for patient selection and only four of the studies reporting length of follow-up. We acknowledge that surgical practice varies between surgeons, hospitals and, indeed, country with regard to length of stay and transfusion rates.…”
Section: S Sumigamamentioning
confidence: 99%
“…2 The purpose of a systematic review is to gather all of the relevant available evidence. Given the practical difficulties of blinding a trial of robot-assisted surgery, by definition, none of the studies could be considered as high quality using the GRADE criteria.…”
Section: Authors' Replymentioning
confidence: 99%
See 1 more Smart Citation